Pastoral care ( Seelsorge ) and spiritual care in Germany - Thierfelder, Constanze (HTS teologiese studies, 2017)
In German-speaking countries the term spiritual care becomes more and more popular, not only in the realm of palliative care but also amongst pastoral care takers. In this article I argue that favouring of the term ‘spiritual care’ is not only a tribute to the changing situation in German-speaking countries, but also a way pastoral care takers want to deal with the challenges they face in a secular, multicultural society. I will discuss whether the use of the term ‘spiritual care’ is a way to ‘lower the profile’ of pastoral care and trying to be less explicit about the institution the pastors represent and the worldview they hold. This might look like an easy escape but does not foster the interaction in a multi-cultural space.